Applied positive psychology improving everyday life, health, schools, work, and society - Donaldson, Stewart I. (Stewart Ian) (Series in applied psychology, 2011)
Determining what works, if anything, in positive psychology / Stewart I. Donaldson -- Core areas in applied positive psychology -- National accounts of well-being for public policy / Edward Diener & Katherine Ryan -- Cultivating positive emotions to enhance human flourishing / Barbara L. Fredrickson & Laura E. Kurtz -- Character strengths and virtues : their role in well-being / Christopher Peterson & Nansook Park -- Applications for improving health, education, and positive human development -- How psychosocial resources enhance health and well-being / Shelley E. Taylor -- Tailoring positive psychology interventions to treat depressed individuals / Nancy L. Sin, Matthew D. Della Porta, & Sonja Lyubomirsky -- Education in 2025 : how positive psychology can revitalize education / Hans Henrik Knoop -- Gallup student poll : measuring and promoting what is right with students / Shane J. Lopez & Valerie J. Calderon -- Improving institutions, organizations, and the world of work -- Applied positive organizational psychology : the state of the science and practice / Ia Ko & Stewart I. Donaldson -- Prosocial practices, positive identity, and flourishing at work / Jane Dutton, Laura Morgan Roberts & Jeff Bednar -- Effects of virtuous leadership on organizational performance / Kim S. Cameron -- Contexts of positive adult development / Jeanne Nakamura -- Future directions for applying the science of positive psychology -- Positive psychology and a positive world-view : new hope for the future of humankind / Mihaly Csikszentmihalyi -- Epilog : a practitioner's guide for applying the science of positive psychology / Stewart I. Donaldson.